“Pundits are saying this is ‘anti-poor’”: competing framing strategies for child road safety policy in the Philippines - Champagne, Sarah N.; Koon, Adam D.; Ulitin, Allan R.; Valverde, Haidee A.; Ashraf, Lamisa; Zarsuelo, Ma-Ann M.; Hoe, Connie; Lam, Hilton Y.; Bachani, Abdulgafoor M. (International journal of health policy and management, 2025)
Background Child restraint systems (CRS) can lead to a 60% reduction in child deaths, yet few low- and middle-income countries (LMICs) have comprehensive policies to enforce best practice standards. In 2019, the Philippines established such a policy: the Child Safety in Motor Vehicles (CSMV) Act. Methods Drawing on framing theory, this study aims to understand the social dimensions of policy change to identify the Act’s origins, design, and implementation. Three sources of data - 25 articles, 27 key-informant interviews, and field notes - were collected and thematically analysed. Results We present the findings according to two features of the framing process: storytelling and naming. The policy process can be sharply distinguished into two sections: the Act’s passage into law (which was swift and successful) and its implementation (which to date has not been). The Act’s implementation was stymied by three overarching frames - that it is “anti-poor,” “unnecessary,” and a “strategic political distraction.” A media backlash at the time of implementation solidified these frames, leading President Duterte to indefinitely defer enforcement of the Act. Conclusion The CSMV Act emphasises that passing a law is insufficient. The trajectory of the act highlights the combined importance of (a) the framing of policy, (b) framing processes operate throughout a policy’s lifecycle, and (c) the media in creating a narrative. Our findings offer valuable insights for other LMICs implementing evidence-based road safety measures, suggesting that successful implementation requires not only strong legislation but also strategic communication and frame management throughout the policy process. Understanding framing dynamics can help policy-makers anticipate and address potential resistance to life-saving public health interventions.